United We Stand, Divided We Fall A Model of Virtual Collaborative Community to Support National Education Agenda - Mat Rahimi Yusof; Hapini Awang; Ramlan Mustapha; Mohd Faiz Mohd Yaakob; Mohd Fairuz Jafar; Mohd Zaini Zakaria; Mohd Yusri Ibrahim (Uitm Pahang, 2024)
Volume 1, Issue 1 (page: 23-28)